Regulation of blood and lymphatic vascular separation by signaling proteins SLP-76 and Syk. - Abtahian, F; Guerriero, A; Sebzda, E; Lu, M; Zhou, R; Mocsai, A; Myers, E; Huang, B; Jackson, D; Ferrari, V; Tybulewicz, V; Lowell, C; et al. (2003)
Lymphatic vessels develop from specialized endothelial cells in preexisting blood vessels, but the molecular signals that regulate this separation are unknown. Here we identify a failure to separate emerging lymphatic vessels from blood vessels in mice lacking the hematopoietic signaling protein SLP-76 or Syk. Blood-lymphatic connections lead to embryonic hemorrhage and arteriovenous shunting. Expression of slp-76 could not be detected in endothelial cells, and blood-filled lymphatics also arose in wild-type mice reconstituted with SLP-76-deficient bone marrow. These studies reveal a hematopoietic signaling pathway required for separation of the two major vascular networks in mammals.